2016
DOI: 10.1590/1678-775720160044
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of Melaleuca alternifolia essential oil on growth and production of volatile sulphur compounds by oral bacteria

Abstract: Objective Halitosis can be caused by microorganisms that produce volatile sulphur compounds (VSCs), which colonize the surface of the tongue and subgingival sites. Studies have reported that the use of natural products can reduce the bacterial load and, consequently, the development of halitosis. The aim of this study was to evaluate the antimicrobial activity of the essential oil of Melaleuca alternifolia on the growth and volatile sulphur compound (VSC) production of oral bacteria compared with chlorhexidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 28 publications
4
24
0
4
Order By: Relevance
“…There are no reported studies that have examined the antibacterial activity of terpinen-4-ol on P. gingivalis and F. nucleatum. Terpinen-4-ol has been shown to be the main active component of Melaleuca alternifolia (TTO) (Hart et al 2000;Nogueira et al 2014), and several studies have reported on the antimicrobial activity of TTO, promoting bactericidal and bacteriostatic effects at low concentrations against P. gingivalis W83 (Graziano et al 2016) and ATCC 33277 (Takarada et al 2004) and against F. nucleatum and P. gingivalis isolates from the oral cavity (Hammer et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…There are no reported studies that have examined the antibacterial activity of terpinen-4-ol on P. gingivalis and F. nucleatum. Terpinen-4-ol has been shown to be the main active component of Melaleuca alternifolia (TTO) (Hart et al 2000;Nogueira et al 2014), and several studies have reported on the antimicrobial activity of TTO, promoting bactericidal and bacteriostatic effects at low concentrations against P. gingivalis W83 (Graziano et al 2016) and ATCC 33277 (Takarada et al 2004) and against F. nucleatum and P. gingivalis isolates from the oral cavity (Hammer et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Different studies investigated the antimicrobial properties of EOs and found that Gram-positive bacteria are more susceptible than Gram-negative bacteria [25]. Tea tree EO (TTEO) is derived from the distillation of leaves and twigs of Melaleuca alternifolia, which contains the following different volatile compounds: terpine-4-ol (≥30%), teripene (about 20%), α-terpinene (about 8%), ρ-cymene (about 8%), α-pinene (about 3%), terpinolene (about 3%), and 1,8-cineol (≤15%) [30]. In terms of medical and aromatic value, rosemary (Rosmarinus officinalis L.) is of considerable importance.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the bactericidal effects, inhibition of growth and adhesion were found against periodontopathogens and cariogenic bacteria (Takarada et al, ). Moreover, bactericidal and bacteriostatic effects on Porphyromonas gingivalis (Pg) and Porphyromonas endodontalis were similar to CHX (Graziano et al, ). The M .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the growth of strains of Pg was effectively inhibited. In comparison with CHX, it had similar antimicrobial activity, promoting bactericidal and bacteriostatic effects at low concentrations (Graziano et al, ).…”
Section: Discussionmentioning
confidence: 99%